The Mechanisms of Polysaccharides from Tonic Chinese Herbal Medicine on the Enhancement Immune Function: A Review - Zhiyi Xie; Ninghua Jiang; Minqiu Lin; Xinglishang He; Bo Li; Yingjie Dong; Suhong Chen; Guiyuan Lv (Molecules, 2023)
Tonic Chinese herbal medicine is a type of traditional Chinese medicine, and its primary function is to restore the body’s lost nutrients, improve activity levels, increase disease resistance, and alleviate physical exhaustion. The body’s immunity can be strengthened by its polysaccharide components, which also have a potent immune-system-protecting effect. Several studies have demonstrated that tonic Chinese herbal medicine polysaccharides can improve the body’s immune response to tumor cells, viruses, bacteria, and other harmful substances. However, the regulatory mechanisms by which various polysaccharides used in tonic Chinese herbal medicine enhance immune function vary. This study examines the regulatory effects of different tonic Chinese herbal medicine polysaccharides on immune organs, immune cells, and immune-related cytokines. It explores the immune response mechanism to understand the similarities and differences in the effects of tonic Chinese herbal medicine polysaccharides on immune function and to lay the foundation for the future development of tonic Chinese herbal medicine polysaccharide products.